HUBUNGAN MUTU PELAYANAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PASIEN (Studi di RSU Dr. Wahidin Sudiro Husodo Mojokerto Tahun 2014) - Angga Zainudin; Hindyah Ike; Nurul Huda (STIKES Insan Cendekia Medika Jombang, 2014)
The lack of quality of nursing care, the nurse do not perform minimum service standard in the set, So thatpatient feel the service provided is not in accordance with costs incurred and the results received service.Minimum service standard in Indonesian hospital in 2013 based on the results of a survey of communitysatisfaction index of 81% of the people are very are satisfied. Standard care hospital in the province of EastJava based community satisfaction index by 86% are satisfied (RI Department of Health, 2013). Meanwhile,in Hospital Dr Wahidin Sudiro Husodo Mojokerto patient satisfaction rate of 75% (Medical Care, 2013).This study aimed analyzing the relationship the quality of nursing care with patient satisfaction studies inHospital Dr. Wahidin Sudiro Husodo Mojokerto.This study used a cross sectional analytic design with a sample population of 219 patients and 44 patientstotaled probability sampling is done by simple random sampling approach. Data processing with editing,coding, scoring, tabulating and software SPSS version 16.0 statistical test